Contradictory findings in the study of emotional false memory: a review on the inadvisability of controlling valence and arousal - Yin, Haochen; Zhou, Yizhou; Li, Zuoshan (Frontiers in Psychology, 2024)
Emotional false memories are the erroneous recollection of events accompanied by an emotional experience. In high-risk domains like psychotherapy and the legal system, emotional false memories are of particular importance. Despite the systematic research conducted on emotional false memories in recent years, findings remain contradictory. Some studies have suggested that negative emotion reduces false memories, while others have suggested that negative emotion increases false memories.Research has mainly employed words and pictures as experimental stimuli, and studies using both types of memory stimuli are reviewed here. From this examination, it emerged that the main reasons for contradictory findings are as follows: (1) different materials have varying effects on inducing false memories, with pictures demonstrating a memory advantage compared to words; (2) recall and recognition tests have been used interchangeably, leading to different false-memory effects depending on the memory test employed; and (3) different studies have adopted different levels of control over valence and arousal when manipulating emotional variables. Future studies should distinguish between the use of different memory materials, examine specific differences in recall and recognition tests, and measure the impact of specific emotions on false memory beyond the dimensions of valence and arousal.